A Corrective Cosmetic Improves the Quality of Life and Skin Quality of Subjects with Facial Blemishes Caused by Skin Disorders - Andra C; Suwalska A; Dumitrescu AM; Kerob D; Delva C; Hasse-Cieślińska M; Solymosi A; Arenbergerova M (Dove Medical Press, 2020)
Cristea Andra, 1 Anna Suwalska, 2 Ana Maria Dumitrescu, 3 Delphine Kerob, 4 Catherine Delva, 5 Marta Hasse-Cieślińska, 6 Agnes Solymosi, 7 Monika Arenbergerova 8 1Private Practice, Bucharest, Romania; 2Primaderm, Warszawa, Poland; 3DClinic, Bucharest, Romania; 4Laboratoires Vichy, Levallois-Perret, France; 5Sylia-Stat, Bourg la Reine, France; 6Proderma, Poznań, Poland; 7Private Practice, Budapest, Hungary; 8Third Faculty of Medicine, Charles University and Kralovske Vinohrady University Hospital, Department of Dermatovenereology, Prague, Czech RepublicCorrespondence: Monika Arenbergerova Email arenbergerova@email.czBackground: Facial blemishes resulting from skin disorders have a significant effect on the patient’s self-esteem and impact quality of life (QOL).Aim: To assess the impact of a corrective cosmetic (CC) on QOL on top of skin quality parameters.Methods: An international observational study was conducted on subjects with visible facial flaws that would benefit from a corrective cosmetic. Investigators collected data regarding demographics, QOL using the Skindex-16 scale, skin dryness and tautness, subject and investigator satisfaction, cosmetic acceptability and tolerance at baseline and after 4 to 6 weeks of daily use.Results: A total of  1840 subjects participated; the mean age was 31.5± 11.1 and 95% were women. Acne accounted for 48.9% of skin conditions, followed by melasma (16.7%) and rosacea (15.3%). Of the subjects 81.2% had at least 10% of the face affected and the condition was rated as disfiguring by 45.3% of the subjects; 45.0% and 44.4%, respectively, had neither taut nor dry skin at baseline. Baseline Skindex-16 scores for symptoms, emotions, functioning and overall were 1.4± 1.3, 3.5± 1.6, 2.4± 1.8 and 2.4± 1.3, respectively, on a scale from 0 to 6. Compliance was 96.0± 10.6%. At the end of the study, Skindex-16 scores had significantly (p< 0.0001) improved for all parameters, as did skin dryness and tautness. Subject and investigator satisfaction were high or very high; cosmetic acceptability was high or very high and local tolerance good or very good.Conclusion: The tested corrective cosmetic significantly improved the QOL of subjects with significant facial flaws, skin tautness and dryness, and was well tolerated.Keywords: corrective cosmetic, dermatoses, quality of life, SKINDEX-16